(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An outline of the comprehension of connection between’s valence electron plasmon optical properties and electricity, for example optical dielectric constant (ε∞) of ternary AIB IIIC VI2 AIIB IVC V2 semiconductors is introduced here. We have made a slideshow an enunciation relating the optical dielectric steady of ternary (AIB IIIC VI2 AIIB IVC V2) chal copyrites with the plasmon energy (ħωp). When plotted on a log log scale against the plasmon energy p (in eV), the dielectric steady of these solids shows a straight relation at the point, and the data points lie on the straight side. We have useful the proposed association these semiconductors tracked down a superior concurrence with the qualities assessed by before scientists.